Strong Photonic Localizations Generated in Single-Optical-Waveguide Ring - Nana Wang; Xiangbo Yang; Xiaohui Xu; Yuehua Huang; Peichao Cao; Dongmei Deng; Chengyi Timon Liu; Xubo Hu (IEEE Photonics Journal)
In this paper, an extreme simple single-optical-waveguide ring (SOWR) is designed to generate strong photonic localizations by considering the similarities between electrons in electronic mesoscopic networks and photons in optical waveguide networks (OWNs). This interesting structure is designed based on the single-electronic-mesoscopic ring that can produce huge electronic persistent currents. We obtain the fitting formulas of the intensity, site number, and site positions for the maximal photonic localization in a SOWR. These interesting SOWRs may provide attractive applications like multichannel high-efficiency energy storages, high power super luminescent light emitting diodes, optical switches, and other correlative all-optical devices. Moreover, the approach of referencing single-electronic-mesoscopic ring to design SOWR may offer a new way to devise optical structures being capable of producing strong photonic localizations and may also deepen people's knowledge on the correlation between OWN and the electronic mesoscopic network.